Quantitative Comparison of Capture-SELEX, GO-SELEX, and Gold-SELEX for Enrichment of Aptamers - Ding, Yuzhe; Liu, Juewen (American Chemical Society, 2023)
Since 1990, numerous methods for aptamer selection have been developed, although a quantitative comparison of their sequence enrichment is lacking. In this study, we compared the enrichment factors of three library-immobilization SELEX methods (capture-SELEX, GO-SELEX, and gold-SELEX). We used a spiked library that contained multiple DNA aptamers with different affinities for adenosine. The aptamer separation efficiency was measured using qPCR, and all of the three methods showed a very low DNA release (<1%) in the presence of 100 μM adenosine. Among these, barely any DNA was released from the gold nanoparticles. Deep sequencing was used to compare the enrichment of three aptamers: Ade1301, Ade1304, and the classical aptamer. Enrichment up to 30 to 50-fold was observed only for the capture-SELEX method, whereas the other two methods showed enrichment factors below 1. By blocking the primer-binding regions of the library, GO-SELEX reached up to 14% enrichment. Finally, the enrichment of aptamers based on nonspecific release and target-induced release was discussed, and the advantages of capture-SELEX were rationalized. Taken together, these results indicate that capture-SELEX is a much more efficient method for enriching aptamers.
This document is the Accepted Manuscript version of a Published Work that appeared in final form in Analytical Chemistry, copyright © American Chemical Society after peer review and technical editing by publisher. To access the final edited and published work see https://doi.org/10.1021/acs.analchem.3c02477